The gas phase conformers and vibrational spectra of valine, leucine and isoleucine: An ab initio study - Supaporn Dokmaisrijan (2018)
The present work reports the results of a conformational study performed on three essential non-polar amino acids: valine, leucine and isoleucine. Ab initio calculations were done at the MP2/6-311++G(2d,2p) level in the gas phase. The 6, 8 and 12 conformers served as a basis to represent the shapes of valine, leucine and isoleucine in the gas phase, respectively, with the relative energies (ΔETotal) below 1.25kcalmol-1compared to the most stable conformer of each amino acid. The ΔETotal values are reported at the MP2/6-311++G(2d,2p) level with corrections for zero-point vibrational energies. The lowest energy conformers of each amino acid contained the intramolecular hydrogen bond (H-bond) interactions between the NH2and COOH groups which are the N-H...O=C, N-H...O-H and O-H...N-H H-bonds. It is obvious that the H-bond interaction plays an important role in the conformational energy and harmonic vibrational frequencies. From the theoretical vibrational spectra, the O-H out of plane and in-plane bending shift ranged from ∼1100cm-1to ∼1360cm-1and the O-H stretching shifts from ∼3600cm-1to 3400cm-1due to the O-H...N-H H-bond interaction. In addition, the side-chain orientations can also affect the conformational stability and diversity, resulting in a large number of low energy conformational minima of amino acid. © 2010 Elsevier B.V.